Effect of Sintering Temperature on the Fabrication of Ceramic Hollow Fibre Membrane - Paiman, Syafikah H; Rahman, Mukhlis A; Othman, Mohd Hafiz Dzarfan; Ahmad, Siti Halimah (ASEAN Journal of Chemical Engineering, 2015)
Recently, ceramic membrane gradually acquired attention from researchers due to the advantages of ceramic’s behavior, which allows the ceramic to overcome the limitations of using polymeric membrane. This work focused on the fabrication of ceramic hollow fibre membrane from a ceramic suspension solution containing yttria-stabilized zirconia (YSZ), polyethersulfone (PESf), N-methylpyrrolidone (NMP) and dispersants using combined phase inversion sintering technique. In this study, ceramic hollow membrane precursors were sintered at different sintering temperature ranging between 1250°C and 1400°C. The influences of sintering temperature on the microstructure, porosity and pore size distribution, mechanical strength and pure water flux of ceramic hollow fibre membrane were investigated in detail. The results show an asymmetric structure of YSZ hollow fibre membrane containing finger-like structure and sponge-like structure. The sponge-like structure can serve as a separation layer, while finger-like-structure performs as a supported layer. It is observed that sintering process caused a significant densification of sponge-like structure (microstructure). Sintering at temperature 1400°C shows the formation of non- interconnected voids. Sintering at 1300°C is sufficient enough having a mechanical strength of 227.55MPa with an apparent porosity of 45.09% and PWF of 118.39L.m¯².hr¯¹.